Macroeconomic Effects and Policy Challenges of Population Aging - Faruqee, Hamid; Tamirisa, Natalia (Washington, D.C. : International Monetary Fund, 2006)
This paper simulates the macroeconomic effects of population aging in a dynamic overlapping generations model of a small open economy. The model is calibrated to data for the Czech Republic, where population aging is proceeding at a pace comparable to that in other advanced countries in Europe. Simulations show that population aging is likely to slow economic growth and improvements in living standards. Although reforms to raise labor force participation and productivity growth can mitigate these adverse effects, they are unlikely to eliminate the need for fiscal reforms. The budget will come under pressure from rising age-related expenditures, and consolidation will be needed to preserve debt sustainability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet